O kościele i kapitule św. Mikołaja w Poznaniu na Zagórzu u schyłku XVIII wieku - Neumann, Piotr Franciszek (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
The church of St. Nicholas most certainly existed already in the first half of the 12th century and was one of the oldest temples in Poznań. It was located at Zagórze, on the right bank of the Warta river, in close vicinity of the Poznań cathedral and the church of the Blessed Virgin Mary in Summo. In the second half of the 15th century it was raised to the status of collegiate and a chapter was created there made up of one praepositus and eight canons. In the 18th century the church had nine altars and four chapels, there was a parish school and a hospital for the poor. Due to massive damages and lack of means for repairs, at the beginning of the 19th century the church was closed and during the second Prussian occupation (most probably in 1817) it was taken down. Today there is no trace of it.